The Reduction of Alcohol Consumption Behavior by Buddhism Integration - Anonjarn, Banyat; Anonjarn, Kanlayawee (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Alcohol consumption in high school or college level is likely to increase every year. Which is a major problem in the country. Drinking affects both the drinkers themselves, families and the society. Thus encouraging those with alcohol drinking habits. Reduce drinking habits. It is very useful. However, the successful reduction of alcohol consumption behavior is possible. Must rely on the principles of various related Buddhism to help support because Thailand is a Buddhist city. This article presents three main components: 1) effects of alcohol consumption. 2) factors related to reducing drinking behavior, 3) Guidelines for reducing alcohol consumption according to the integrated Buddhism guidelines. This is information derived from the author's review of the literature.